Feasibility of Electronic Patient-Reported Outcome Measures following Spinal Injuries in Tanzania - Sabas, Romani Roman; Woodfield, Julie; Ikwuegbuenyi, Chibuikem A.; Mchome, Laurent Lemeri; Shabhay, Zarina; Cadieux, Magalie; Makubi, Abel; Mangat, Halinder S.; Härtl, Roger; Shabani, Hamisi Kimaro (WFNS Journal, 2025)
Traumatic spinal injuries are common in resource-limited environments and cause severe consequences such as pain, weakness, numbness, impaired bladder, bowel and sexual function, financial burdens, and psychological issues. In-person follow-up is challenging due to financial constraints, physical disability, and limited transportation. Our study aimed to explore the feasibility of using electronic patient-reported outcome measures (PROMs) following spinal injuries in Tanzania.From March to June 2023, we prospectively recruited 50 consecutive inpatients with traumatic spinal injuries at Muhimbili Orthopedic Institute in Tanzania. We recorded mobile phone and internet access and administered the Kiswahili-validated version of the SF-8 quality-of-life (QoL) questionnaire. We compared completion rates between in-person and electronic versions in-hospital and assessed postdischarge completion for electronic questionnaires.A total of 50 participants were included (mean age: 33 years [standard deviation, SD: 14], 43/50 [86%] male). Most had access to a mobile phone (47/50, 94%), and 27/50 (54%) had access to a smartphone. Only 10 participants (20%) completed the electronic PROM. Reasons for lack of completion were: no internet-enabled device (23/50, 46%), internet connectivity (9/50, 18%), unfamiliarity to the electronic forms (5/50, 10%), and lack of motivation to respond (3/50, 6%). All participants completed the in-person SF-8. Post-injury scores were lower than those reported pre-injury (Physical Component Summary Mean: 37(SD:14) v 95(SD:8), Mental Component Summary Mean: 52(SD:19) vs.98(SD:4)).Electronic PROMs following spinal injuries have low completion rates in Tanzania. In-person inpatient QoL assessment highlighted the significant impact of spinal injuries, emphasizing the importance of developing methods of QoL assessment.
Keywords: spinal injuries; quality of life; feasibility; electronic questionnaires; Tanzania; Patient Reported Outcome Measures